ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU WASPADA STROKE PADA KELOMPOK RESIKO TINGGI DI WILAYAH KERJA PUSKESMAS PONCOKUSUMO MALANG (PENDEKATAN TEORI HEALTH PROMOTION MODEL NOLLA J PENDER) - Rahmania Ambarika* Achdiat Agoes** Heri Kristianto*** (The Indonesian Journal of Health Science, 2016)
Stroke is main health problem in sociaty because  can cause death, disability and decreasing life quality significantly. Prior problem that cause increasing mortality and disability is lack of awareness of people on knowing the early sign of stroke. This study purpose is to knowing the relating factor wit h awareness behaviour of stroke from high risk people. This study was analityc deskriptif with cross sectional. Sample taken is 144 people with purposive sampling. Bivariat analysis show there is relation between prior related behaviour (p = 0,000), personal factor (p = 0,000), perceived benefits (p = 0,000), perceived barrier to action (p = 0,000), activity related effect (p = 0,000), and interpersonal factor ( p = 0,000) with awareness behaviour. Factor that isnot having relationship with stroke behaviour  is perceived self efficacy ( p = 0,000). The most close relation factor with awareness behaviour is knowledge perceivedbarrier to action and prior related before. Experiment before about stroke is become stimuly factorthat form perception and behaviour ba sed on knowledge that will perform long last behaviour.